Latin America and the global Cold War - Field, Thomas C. Herausgeber; Krepp, Stella Herausgeber; Pettinà, Vanni 1978- Herausgeber (The new cold war history, 2020)
"Latin America and the Global Cold War analyzes more than a dozen of Latin America's forgotten encounters with Africa, Asia, and the Communist world, and by placing the region in meaningful dialogue with the wider Global South, this volume produces the first truly global history of contemporary Latin America. It uncovers a multitude of overlapping and sometimes conflicting iterations of Third Worldist movements in Latin America, and offers insights for better understanding the region's past, as well as its possible futures, challenging us to consider how the Global Cold War continues to inform Latin America's ongoing political struggles"--